Modulation of Jagged1 processing by the E6 oncoprotein of Human Papilloma Virus - Lempinen, Valtteri (My University, 2023)
Virtually all cervical cancer (CC) cases are caused by high-risk human papillomaviruses (hr-HPV). HPVs carcinogenicity is caused by viral oncoprotein's ability to hijack and degrade host proteins. Particularly, the E6 oncoprotein can bind and degrade PDZ (PSD-95, Dlg1, ZO-1) proteins. One of the well-known Notch pathway ligands, Jagged1 (JAG1), correlates with poor clinical prognosis of CC. JAG1 is similarly cleaved as the Notch receptor: an extracellular cleaving removes the N-terminal end of JAG1, producing a membrane-tethered C-terminal fragment (CTF). The CTF is cleaved at its transmembrane domain, releasing JAG1s' intracellular domain (JICD). The JICD harbors a PDZ binding domain (PBM) like the E6 oncoprotein. We hypothesize that HPV targets JAG1 in a PDZ-dependent manner. Little is known about the role of JAG1 and its processing in CC. This project aims to determine the modulation of the JAG1 processing in CC and the participation of JICD in cervical carcinogenesis. Endogenous JAG1 and JICD expressions were evaluated within CC-derived cell lines (CaSki, SiHa, and HeLa) and immortalized keratinocytes (HaCat). The expression of JAG1 and cleaved form were also evaluated after E6 oncoprotein overexpression. Mutant JAG1 and JICD devoted to their C-terminal PBM were co-expressed with E6 to determine its participation in JAG1 cleaving modulation. Cell proliferation after JAG1, JICD, and their C-terminal mutant forms overexpression were evaluated by crystal violet and cell count. We found that E6 overexpression in HaCat, CaSki, and HeLa correlates with increased JAG1 and JICD expression. We also showed that the E6 oncoprotein modulates JAG1 processing. Of note, JAG1 and JICD decrease cell proliferation, an activity that is abrogated by removing the C-terminal PBM. These results strongly suggest that JAG1 processing is modulated by its C-terminal PBM and that the HPV E6 oncoprotein modulates this process.
Keywords: Cervical cancer, HPV, Notch, JAG1, Oncoprotein